AREAS OF SCIENTIFIC RESEARCH AT HIGHER SCHOOL OF PEDAGOGICAL EDUCATION IN SIBERIA IN 1960-1980s - Valeriy V. Petrik (Высшее образование в России)
The article is dedicated to the activities of the institutions of higher pedagogical education in Siberia aimed at the development of the main scientific areas of research in the 60s-80s of the 20th century. On the basis of the documents and materials from the archives the most prominent achievements of the scientists of teacher training universities of the region in the leading branches of education are being analyzed.